DE LA GESTION DE CONFLIT A LA COMMUNICATION NON VIOLENTE Par - ALALY LIKUNDE, Simon- pierre; MBOLE, Laurent ALEMO; BONGENDE, Léa MBASA (IJRDO - Journal of Applied Management Science, 2017)
This work concerns communication as source of conflict. The concern articulated around the following question: what are the points of report between communication and conflict? The objective of the study is to determine points of report between communication and conflict. The hypothesis is the following one: the points of report between communication and conflict would be multiple, in particular: conflict which can go out of the transmitter, or the decoder, or the code; the problem of gallows and the flash of lightning; the problem latent speech and pronounced speech; the problem of the factors of communication; the problem of language and the unconscious and the problem of significant, meant and of referent establish(constitute) important facts which enter games(sets) in the communication and susceptible to plunge people into the dispute. We used the documentary technique where we consulted some works in our carried (worn). The following conclusions are found: there is a narrow report (relationship) between the communication and the conflict on many possible points such as raised (found) above.